The Influence of Human Resource Interactions on Loyalty with Patient Satisfaction as an Intervening Variable in Hospital X Surabaya - Minarni Wartiningsih (YCAB Publisher, 2024)
Background: In the hospital industry, human resources are the drivers of the organization to achieve goals. The interaction of hospital human resources with patients is one of the essential aspects of service to increase patient satisfaction and loyalty. Objective: This study aimed to determine the effect of hospital human resource interactions on loyalty through patient satisfaction as an intervening variable. Methods: This type of research is quantitative analytic with a cross sectional design. The sampling technique was 339 respondents using random sampling technique. The data obtained will be analyzed using SmartPLS software (v3.2.9). Result: Interaction has a significant effect on patient loyalty directly (β=0.161 and p-value=0.015). Interaction also affects patient loyalty through intervening patient satisfaction variables (β=0.094 and p-value = 0.049). Conclusion: This study concludes that interaction has more effect on patient loyalty directly than through the intervening variable of patient satisfaction.